'They should walk with you': the perspectives of African Americans living with hypertension and their family members on disease self-management. Issue 3 (3rd April 2023) - Woods, Sarah B.; Hiefner, Angela R.; Udezi, Victoria; Slaughter, Gabriele; Moore, Rachel; Arnold, Elizabeth Mayfield
ABSTRACT: Objectives: African Americans are at significantly greater risk for hypertension, as well as worse hypertension-related morbidity and mortality than other racial/ethnic groups. Prior research aiming to address these health disparities has focused on improving individual patient self-management, with few studies testing family-centered interventions. We aimed to explore the perspectives of African Americans with hypertension and their family members on hypertension, self-management, and reciprocal family-hypertension impacts to inform future intervention design. Design: We conducted four dyadic focus groups (90–120 minutes) of African American adults with hypertension (i.e. patients) and their family members. We recruited patients ( n  = 23) and their family members ( n  = 23) from four African American-serving Christian churches over a period of three months (69.6% female, M age = 60.73 years). Patient–family member dyads were interviewed conjointly (groups ranged from 4 to 6 dyads, each) by facilitators using open-ended questions to elicit perspectives regarding contributors to hypertension, self-management strategies, family influence on self-management, and the impact of hypertension on the family. A grounded theory approach was used for analysis. Results: Participants' responses highlighted themes of societal risk factors and barriers (e.g. racism-related stress worsens blood pressure), influences of African American culture (e.g. culturally-informed diet practices), the patient–physician relationship (e.g. proactive communication is beneficial), family-level influences on health (e.g. family monitoring patients' health behaviors), and patient-level risk factors and self-management strategies (e.g. prayer to cope with stress). Themes reflected a hierarchical, nested, ecological structure such that themes within unique levels of participants' social systems affected, and were affected by, stress, change, or behavior in the other levels. Conclusions: African American adults with hypertension and their family members described multilevel influences on hypertension and disease self-management, with a strong emphasis on the value of family support. Developing culturally appropriate, family-centered interventions to improve hypertension self-management will be an important next step.